METODE DEMPSTER-SHAFER UNTUK SISTEM PAKAR DETEKSI KERUSAKAN MESIN CUCI BERBASIS WEB - Laila Septiana (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2015)
A front loading washing machine is one household items needed in daily life. But its use is often experienced problems caused obstacles both human error and resilience of spare parts has limited capacity. To resolve this may be accomplished by novice technicians who have the basic skills of a front-loading washing machine. But sometimes to overcome these problems also requires a high level of ability of front-loading washing machines that require a qualified technician to fix it. Shafer Demster method used to combine separate pieces of information ( evidence ) to calculate the probability of an event. So that the application of such methods in an expert system to detect damage to the front loading washing machine with a problem-solving solution is expected to provide appropriate